Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I solve this limit without using L'Hopital's rule, if at all possible?

$$ \lim_{h\to0}\frac{1 - 2^{-h}}{h}$$

share|cite|improve this question
Have you defined the constant $e$? If so, how? – JavaMan Jan 4 '13 at 21:46
up vote 2 down vote accepted

Note that $$\lim\limits_{x\to{0}}{\left( 1+x \right)^{\tfrac{1}{x}}}=e$$ is equivalent (by continuity of $\log{}$ function) to $$\lim\limits_{x\to{0}}{\dfrac{\log_a(1+x)}{x}}=\log_a{e}=\dfrac{1}{\ln{a}}.\;\;(a>0,\; a\ne{1}) \tag{*}$$ Substitute $t=\log_a(1+x),$ then $1+x=a^t, \;\; x=a^t-1$ and rewrite $({}^*)$ as $$\lim\limits_{t\to{0}}{\dfrac{t}{a^t-1}}=\dfrac{1}{\ln{a}}$$ or $$\lim\limits_{t\to{0}}{\dfrac{a^t-1}{t}}=\ln{a}.$$

share|cite|improve this answer
This one was most clear to me. Thank you. – Ataraxia Feb 5 '13 at 0:16

Observe $$\lim_{h\to 0}\frac{1-2^{-h}}{h}=-\lim_{h\to 0}\frac{2^{-h}-2^{-0}}{h}=...$$ (Hint: Define the derivative of $2^{-x}$ at $0$)

EDIT: The definition of the derivative of $2^{-x}$ at $0$ is $$\lim_{h\to 0}\frac{2^{-h}-2^{-0}}{h}$$ But that is $(2^{-x})^{\prime}(0)=(-\ln 2\cdot 2^{-x})(0)=-\ln 2\cdot 2^0=-\ln 2$

share|cite|improve this answer
I'm not seeing it :( I see how you did that, but what do you do from there to get ln(2)? – Ataraxia Jan 4 '13 at 22:00
He/She 's just saying that this is, by definition, the (negative of) the derivative of the function $2^{-x}$ at the point $0$. If $f(x) =2^{-x}$, then you're looking for $-f'(0)$. So if you know how to find this derivative, you're done. – Brusko651 Jan 4 '13 at 22:02

You can expand the Numerator as a power series.

Using $e^x = 1 + x + \frac{x^2}{2!} + \frac{x^3}{3!} \dots$,

$$2^{-h} = e^{\log(2) \cdot (-h)} = 1 - \log(2)\cdot h + \frac{(\log(2)\cdot h)^2}{2} \dots$$

Therefore $$\lim_{h\to0}\frac{1 - 2^{-h}}{h} = \lim_{h\to0}\frac{\log(2)\cdot h - \frac{(\log(2)\cdot h)^2}{2} \dots}{h} = \lim_{h\to0} \left( \log(2) - \frac{(\log(2))^2h}{2} \dots \right) = \log(2)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.